Laporan kasus keracunan Chlorophyllum cf. molybdites di Surabaya, Indonesia - Ivan Permana Putra (Fakultas Pertanian Universitas Ichsan Gorontalo, 2021)
Wild mushrooms are one of the agricultural commodities used as food by Indonesian. However, the risk of poisoning can occur due to the morphology which often similar between edible and poisonous mushrooms. One family consumed wild mushroom which found around their residential area in Surabaya. The macrofungi grew on the grass near the ‘sengon’ trees around it. A few hours later, all of them experienced vomiting and diarrhea. The entire family rushly evacuated to the nearest hospital and received treatment. The blood tests and computed tomography (ct) scan of the abdomen showed no serious effect in all victims. The mushroom which caused poisoning then documented completely. The identification results using several macroscopic characters confirmed the macrofungi as Chlorophyllum cf. molybdites. This mushroom is known as in the category of V poisonous mushrooms which cause irritation of the digestive tract. This report indicates the need for a better understanding of the wild mushrooms identification for consumption. This is one of the approach to prevent wild mushroom poisoning in Indonesia.